Evaluation of the Limb Symmetry Index: The Side Hop Test - Mirković, Sanja V.; Đurić, Saša; Sember, Vedrana; Knezevic, Olivera M.; Pajek, Maja; Mirković, Milan M.; Mirkov, Dragan M. (Frontiers in Physiology, 2022)
The main objective of present study was to evaluate inter-rater reliability and concurrent validity of Side Hop Test stopwatch vs. force plates timing, and to determine the number of sessions and trials required to minimize the effects of learning on Side Hop Test total time and limb symmetry index. Fifteen healthy male physical education students (mean ± SD: age, 23 ± 3 years; height, 181 ± 9 cm; and weight 72 ± 6 kg) participated. Side Hop Test total time (stopwatch and force plates) of left and right leg, and limb symmetry index (force plates) were obtained over 7 sessions conducted 5–7 days apart. Time recordings of two raters were similar (t = -0.56, p>0.05) with high reliability (all ICC >0.99 and CV% <0.1) and no systematic bias when compared to force plate data (p>0.05; for rater one and two, respectively). Total time improved across the Sessions (F = 25.87, p<0.01, ω2 = 0.18) and Trials (F = 68.15, p<0.01, ω2 = 0.10), with no significant interaction between factors. No between-leg differences were detected (F = 0.52, p>0.05, ω2 = 0.001). Limb symmetry index ranged from 0.999 to 1.055 across all sessions and trials (all p>0.05 and ω2 < 0.00). Stopwatch measurements could be reliably used to measure total time in the Side Hop Test, while the test could be administrated with only one experienced rater. Unlike total times, findings on limb symmetry index suggest it could be reliably assessed after only few familiarization trials.